1985
DOI: 10.1172/jci111673
|View full text |Cite
|
Sign up to set email alerts
|

Asialo von Willebrand factor interactions with platelets. Interdependence of glycoproteins Ib and IIb/IIIa for binding and aggregation.

Abstract: Asialo von Willebrand factor (AS-vWf) binds to and aggregates normal human platelets in the absence of ristocetin. Maximal specific binding of AS-vWf is 1-2 ug vWf protein/108 platelets.Despite the specificity of the binding, only 60% of the bound AS-vWf can be dissociated after equilibrium has been reached. We investigated the site of binding and the mechanism of aggregation of platelets by AS-vWf by (a) pre-incubating platelets with either of two monoclonal antibodies, one against glycoprotein lb (GPIb) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
1

Year Published

1985
1985
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 91 publications
(32 citation statements)
references
References 26 publications
3
28
1
Order By: Relevance
“…48,63-66 A body of literature has firmly established that VWF and ␣ IIb are essential for thrombus formation at the vascular injury site, whereas platelet ␣-granule-derived TGF-␤ and PDGF are major players of endothelial cell proliferation and vessel repair. [67][68][69][70] In addition, TGF-␤1 has been shown to enhance platelet aggregation through a nontranscriptional effect on the fibrinogen receptor. 71 Furin has also been identified as the convertase responsible for the maturation of Notch-1, a cell-surface receptor involved in multiple developmental processes.…”
Section: Discussionmentioning
confidence: 99%
“…48,63-66 A body of literature has firmly established that VWF and ␣ IIb are essential for thrombus formation at the vascular injury site, whereas platelet ␣-granule-derived TGF-␤ and PDGF are major players of endothelial cell proliferation and vessel repair. [67][68][69][70] In addition, TGF-␤1 has been shown to enhance platelet aggregation through a nontranscriptional effect on the fibrinogen receptor. 71 Furin has also been identified as the convertase responsible for the maturation of Notch-1, a cell-surface receptor involved in multiple developmental processes.…”
Section: Discussionmentioning
confidence: 99%
“…EDTA added in vitro inhibits the platelet aggregation of the PRP of platelet-type vWd seen after adding cryoprecipitate or plasma and the post-DDAVP platelet aggregation in type Ilb vWd patients (2,5,23). Calcium ions are also necessary for the platelet aggregation that occurs after addition of AS-vWf to platelets (see below) (7)(8)(9)(10)25).…”
Section: Discussionmentioning
confidence: 99%
“…Asialo vWf (AS vWf) has been shown to aggregate normal platelets in the absence of ristocetin (7)(8)(9)(10)25). We and others have recently shown that AS-vWf binds to both the GPIb and the GPIlb/IlIa complexes (10, 1 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Platelets Solum) were tested. The vWf was purified as previously described (13). The monoclonal antibody 6D1 is directed against the site on GPIb which vWf binds in the presence of ristocetin (14).…”
Section: Methodsmentioning
confidence: 99%